1996
DOI: 10.1006/viro.1996.0667
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Regulatory Functions of the HSV-1 Immediate-Early Protein ICP22

Abstract: Previous work has shown that the 68-kDa immediate-early protein of herpes simplex virus type 1 (HSV-1), also known as ICP22, is involved in the control of viral gene expression, although the precise mechanism remains to be elucidated. In order to study the function(s) of this protein, we constructed expression vectors containing the coding sequence of the ICP22 gene placed under the control of the SV40 or HCMV promoter. After cell transfection, ICP22 synthesis was studied by immunoblotting, using a specific an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 0 publications
2
28
1
2
Order By: Relevance
“…Repression of the ORF62 promoter by ORF63 was observed previously in transient-transfection assays in one report (20) but not in another (29). The herpes simplex virus homolog of the ORF63 protein, ICP22, can repress viral immediate-early promoters, including the promoter for ICP4, the homolog of the VZV ORF62 protein, in transient-transfection assays (45). In contrast to these transienttransfection studies, our experiments analyzed the effect of ORF63 in the context of the whole VZV genome, with levels of ORF63 appropriate for infected cells and with the ORF62 regulatory and coding sequences in the viral genome.…”
Section: Discussionmentioning
confidence: 71%
“…Repression of the ORF62 promoter by ORF63 was observed previously in transient-transfection assays in one report (20) but not in another (29). The herpes simplex virus homolog of the ORF63 protein, ICP22, can repress viral immediate-early promoters, including the promoter for ICP4, the homolog of the VZV ORF62 protein, in transient-transfection assays (45). In contrast to these transienttransfection studies, our experiments analyzed the effect of ORF63 in the context of the whole VZV genome, with levels of ORF63 appropriate for infected cells and with the ORF62 regulatory and coding sequences in the viral genome.…”
Section: Discussionmentioning
confidence: 71%
“…Since previous studies have suggested that ICP22 can repress transcription from a large number of promoters in transient re- porter assays, we wanted to determine if ICP22 can repress expression from its own promoter (13). To this end, Vero cells were transfected with the ICP22 promoter-luciferase construct and increasing amounts of pCDNA3:22ORF.…”
Section: Resultsmentioning
confidence: 99%
“…Initial studies by Prod'hon et al (13) examined the effect of expression of ICP22 on HSV promoter activity. In contrast to its role in upregulating late viral gene expression during infection, cotransfection of ICP22 alone with a panel of HSV-1 promoters repressed transcription of reporter genes.…”
Section: Replication Of Icp22mentioning
confidence: 99%
“…To a degree, all kinetic classes of viral genes are affected during infection with ICP22 Ϫ viruses. Although ICP22 is required to achieve wild-type levels of viral proteins in infected cells, it has been reported that ICP22 negatively regulates expression from viral promoters in transient-transfection assays (22,33). Because ICP22 is able to both up-and downregulate gene expression under different conditions, it is possible that its role may be to control the regulation of viral gene expression.…”
Section: Icp0mentioning
confidence: 99%